The Study of Classroom Management Styles of Faculty Members in Kashan University of Medical Sciences Iran - Mohammad Amini; Hamid Rahimi; Zahra Gholamian (Kerman University of Medical Sciences, 2015)
Background & Objective: Classroom management is a key variable in creating a desirable environment for students training and learning Today equipping professors with managerial skills in planning for professional education especially medical education is necessary Thus the aim of this research was to investigate classroom management styles of faculty members in Kashan University of Medical Sciences Iran   Methods: This was a descriptive survey The statistical population consisted of all faculty members of Kashan University of Medical Sciences (n = 182) Through stratified random sampling method 114 individuals were selected We used a standard questionnaire to assess classroom management styles The questionnaire consisted of 25 4point items and 3 styles of education management (questions 1 to 13) people management (questions 14 to 21) and behavior management (questions 22 to 25) based on 3 approaches (interventional interactive noninterventional) The validity of the questionnaire was confirmed using content validity The reliability of the questionnaire was also confirmed using Cronbachs alpha coefficient ( ;alpha = 082) Data analysis was performed using descriptive statistics (frequency percentage and mean and standard deviation) and analytical statistics (ANOVA and Students independent t tests)   Results: The mean of each classroom management style was higher than the estimated average (25) The highest average was that of education management style (275) Based on the obtained means classroom management (6828) was an interventional approach   Conclusion: Findings showed that university faculty members respectively have the highest regard for education management and people management and the least regard for behavior management